Mindful parenting: associations with parental depression and well-being - Miner, Rachel, author; Coatsworth, Doug, advisor; Schmid, Arlene, committee member; Shomaker, Lauren, committee member (Colorado State University. Libraries, 2019)
This study investigated the association between mindful parenting and both parent depression, and parent well-being. Current research has found that many individuals experience stress in parenting, which impacts their overall well-being, possibly leading to depressive symptoms. Mindfulness has been found to counteract negative effects of stress. However, much of the research has neglected to focus on the effects of mindful parenting, as opposed to only trait mindfulness skills, as well as general stress as opposed to parenting stress specifically. Mindfulness also appears to differ by gender. In a sample of four hundred and thirty-two families, this study tested the association between mindful parenting and both parent depression and parent well-being, after controlling for trait mindfulness practices as well as SES and parenting stress. Results indicated that mindful parenting was associated with parent depression and parent well-being independently and uniquely after controlling for trait mindfulness, income, and parenting stress. Parent gender was not significantly associated with depression or well-being outcomes. Conclusions of this study indicate a need for incorporating mindful parenting into parenting interactions as a way to combat the negative effects of parenting stress.